POST-PEASANT MARGINALIZATION: EDUCATION AND INCOME IMPLICATION - Kusumastuti, Ayu (PEOPLE: International Journal of Social Sciences, 2018)
Peasant is an occupation mostly found in rural areas. Peasant has no land (landless agriculturalist) and only cultivates the landlord’s land (Holmes, 1983, p. 734). In this situation, peasant tends to be marginalized or receives no rights in agricultural production factors, loan access and even market access. This is worsen by the entry of capitalism to the rural areas that marginalizes the peasant’s right even more. Marginalization to peasant continues. Here, the author called it as Post-Peasant Marginalization. Post-peasant marginalization shows that being lack of rights to the agricultural resources, peasant will still and continue to be in the life circle without fulfillment of basic needs of education and economy, which in this case, the income. Using quantitative method, the author conducted a survey in 3 villages in Tumpang Subdistrict: Wringinsongo Village, with the sample of 45 respondents, Jeru Village of 48 respondents and Pulungdowo Village of 48 respondents. With Kendall correlation analysis with the significance rate of 5% between the variable of education level and income, it was found that the score of .sig was 0.00; 0.001; 0.001 respectively which was less than the score of .sig 0.005 that shows the significant relation between the level of education and level of income. It was found that the majority people in the village who works as peasant have only elementary school education and monthly income between IDR 500.000-IDR 1,000,000 or between 38USD-75USD. This shows that the low education is correlated to the low income. The low aspect of education and economy has indicated that peasant has still no access to decent life. Peasant has been the marginalized community in the midst of massive development in all sectors. Post-peasant marginalization shows that being lack of rights to the agricultural sector, peasant will still and continue to be in the poor life circle as indicated by the low level of education and level of income.